2005
DOI: 10.2139/ssrn.842104
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Global Equity Indexes to U.S. Monetary Policy Announcements

Abstract: This paper documents the impact of U.S. monetary policy announcement surprises on equity indexes in sixteen countries, covering both developed and emerging economies. Using high-frequency intraday data, I find a large and significant response of Asian, European, and Latin American equity indexes to U.S. monetary policy announcement surprises at short time horizons. In this paper, I use two proxies for monetary policy surprises: a surprise change to the current target federal funds rate, and a revision to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
102
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(112 citation statements)
references
References 18 publications
10
102
0
Order By: Relevance
“…6 Reactions of investors in emerging financial markets to news may be different than those in industrial countries due to several factors including weak monetary authorities, limited investor confidence, inefficient financial markets and differences in their exchange rate regimes as well as the degree of integration of their markets with the global financial system (for further discussion and empirical evidence, see Serwa (2006), Wongswan (2009) and Hausman and Wongswan (2011)). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6 Reactions of investors in emerging financial markets to news may be different than those in industrial countries due to several factors including weak monetary authorities, limited investor confidence, inefficient financial markets and differences in their exchange rate regimes as well as the degree of integration of their markets with the global financial system (for further discussion and empirical evidence, see Serwa (2006), Wongswan (2009) and Hausman and Wongswan (2011)). …”
mentioning
confidence: 99%
“…They found that the verbal comments of policy makers in the Czech Republic, Hungary, and Poland influenced behavior of the currency market but that this effect differed 7 See, among others, Ganapolsky and Schmuckler (2001), Kaminsky and Schmukler (2002), Korczak and Bohl (2005), Nikkinen, Omran, Sahlström and Äijö (2006), Robitaille and Roush (2006), Wongswan (2009), Hanousek, Kočenda and Kutan (2009). There is only a limited number of papers concerning other market segments (see e.g.…”
mentioning
confidence: 99%
“…The importance of the news revealed in the FOMC meeting can be even further highlighted by the impact it has on foreign markets (see e.g. Wongswan, 2009;Hausman and Wongswan, 2011;and Lucca and Moench, 2014), and different asset classes (see e.g. Basistha and Kurov, 2014, for the impact of FOMC announcements on energy prices; and Andersen et al, 2007, for the impact on international equity, bond and foreign exchange markets).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A large body of literature examines responses of financial market prices to the surprise component of major macroeconomic announcements and monetary policy releases (Andersson, Overby, and Sebestyén, 2009). Several studies focus on the impact of monetary policy surprises on interest rates (Valente, 2009;Das, 2002;Ederington and Lee, 1993;Doukas and Melhem, 1986;Urich and Wachtel, 1984;Grossman, 1981) and more recently on global equity indexes (e.g., Wongswan, 2009), bond and stock markets (Basistha and Kurov, 2008;Andersson, 2007;Beber and Brandt, 2006;Deaves, 1990), and foreign exchange rates (Andersen, Bollerslev, Diebold, and Vega, 2007;Faust, Rogers, Wang, and Wright, 2007;Andersen, Bollerslev, Diebold, and Vega, 2003).…”
Section: Introductionmentioning
confidence: 99%